Application of a micromechanical model to wave propagation through nonlinear rough interfaces under stress - Marangos, Orestes; Misra, Anil S. (My University, 2006)
Imperfect interfaces between two rough solids are known to exhibit nonlinear, anisotropic behavior under static normal and shear stresses. We expect this nonlinear, anisotropic behavior to have a profound effect on wave propagation through such interfaces. A micromechanical methodology is applied to explicitly model the initial normal and shear stiffness behavior of interfaces. The calculated initial normal and shear stiffness are used to investigate plane wave propagation behavior through interfaces utilizing the imperfectly bonded interface model © 2006 IEEE.
Keywords: Anisotropy; Interfaces; Nonlinear; Reflection coefficient; Transmission coefficient